Morpho-histopathological characteristics and molecular identification of fasciola species from infected cattle liver - Omar, Abdullahi Abdirisak (2023)
Fasciola species, parasitic trematodes of mammals and humans, pose a significant public health risk and carry substantial socio-economic consequences. There have been few studies in Kelantan to characterise species, and this study focuses on their morphohistological characteristics and molecular identification. Infected cattle livers were collected from several farms in Kelantan. Morphometric parameters for juvenile, medium, and adult flukes such as body width (BW), body length (BL), cone width (CW), and cone length (CL) were determined using a calibrated stereomicroscope. Fluke genomic DNA was extracted using a QIAGEN Mini kit, and polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) was performed on the 463 bp DNA fragment in the region of internal transcribed spacer 1 (ITS1) using Tas1 restriction enzyme. The PCR-RFLP product was separated on agarose gel and photographed, the livers were grossly investigated for Fasciola infection and morphological changes. Tissue samples were collected from histopathological examinations using H & E stain and the pathological macroscopic and microscopic changes of the liver and gall bladder were observed. The morphometric analysis of adult flukes revealed a BL of 4.260 ± 0.191cm, BW of 0.61 ± 0.180 cm, cephalic CW of 0.37 ± 0.057 cm, and CL of 0.28 ± 0.058 cm. The BL/BW and BW/CW ratios were 2.93-5.97 cm and 1.55-2.72 cm respectively. The PCR-RFLP produced 3 bands of 93 bp, 151 bp, and 220 bp, which indicated as F. gigantica. The parasite was found in the liver and gall bladder, and thickening of bile duct mucous was observed on macroscopic examination. Microscopic observation found infiltration of inflammatory cells, fibrosis, necrosis, and degeneration of hepatocytes. In the gall bladder, necrosis was found in the epithelial mucosal bile duct, infiltration of collagen fibers, inflammatory cells, hypertrophy, and hyperplasia of the bladder epithelium. The study found that the combination of both morphometric analysis and molecular methods can accurately confirm the presence of F. gigantica in the infected liver. Histopathological characterisation has demonstrated different morphological features of infected cattle liver.